A cross-sectional study on risk factors and their interactions with suicidal ideation among the elderly in rural communities of Hunan, China. Issue 4 (15th April 2016) - Xu, Huilan; Qin, Lulu; Wang, Jinhong; Zhou, Liang; Luo, Dan; Hu, Mi; Li, Zhenhua; Xiao, Shuiyuan
Abstract : Objectives: To identify risk factors, and their interactions, for suicidal ideation among the elderly in rural communities of Hunan and to provide some scientific basis for suicide prevention. Design, setting and participants: A cross-sectional survey was conducted among the elderly in rural communities in China's Hunan Province. Thirteen areas were selected by multi-staged cluster random sampling, and 1887 rural elders were investigated via face-to-face interviews. Main outcome measures: Measures included sociodemographic information, suicidal ideation, activities of daily living (ADL), major depression disorder (MDD), drinking, stressful life events and social support. Non-conditional logistic regression was preformed to explore the influencing factors for suicidal ideation, and additive interaction was used to analyse the interaction between risk factors. Results: Incidence of suicidal ideation among the elderly was 14.5% (95% CI 12.9% to 16.1%) in rural communities of Hunan. The independent influencing factors for suicidal ideation were annual personal income (OR 3.14; 95% CI 2.15 to 4.59), MDD (OR 17.04; 95% CI 11.91 to 24.39), chronic diseases (OR 2.99; 95% CI 1.84 to 4.85) and ADL (OR 2.00; 95% CI 1.37 to 2.94). Additive interactions were detected between MDD and ADL with a relative excess risk of interaction (RERI) of 21.18 (95% CI 5.47 to 36.89), and between MDD and annual personal income with an RERI of 35.00 (95% CI 9.00 to 61.00). Conclusions: The independent risk factors for suicidal ideation are annual personal income (≤2200 CNY), MDD, chronic diseases and disabled ADL status. MDD has additive interactions with ADL and annual personal income. These findings have significant implications for the prediction and prevention of suicidal behaviours.